2019
DOI: 10.1016/j.ejpb.2019.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Determination of drug-polymer solubility from supersaturated spray-dried amorphous solid dispersions: A case study with Efavirenz and Soluplus®

Abstract: Amorphous solid dispersions (ASDs) are found to be a well-established strategy for overcoming limited aqueous solubility and poor oral bioavailability of active pharmaceutical ingredients (APIs). One of the main parameters affecting ASDs physical stability is the API solubility in the carrier, because this value determines the maximal API load without a risk of phase separation and recrystallization. Phase-diagrams can be experimentally obtained by following the recrystallization of the API from a supersaturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
2
9
0
3
Order By: Relevance
“…It was shown that Pluronic ® F-127 showed a delay in release at acidic pH; however, at alkaline pH, it showed a significant improvement in API solubility, which was confirmed in the tests performed [54]. On the other hand, Soluplus shows the lowest solubility in acidic pH and the highest in alkaline pH; in the study, it was shown that the systems containing the polymer showed better solubility at higher pH, which confirms the assumption that the solubility of the entire system will depend on the solubility of the polymer used to compose the physical mixture [55,56]. The obtained results indicate the potential development of formulations containing carvedilol as an active substance based on selected polymers, allowing API release in a selected pH-dependent environment.…”
Section: Resultssupporting
confidence: 64%
“…It was shown that Pluronic ® F-127 showed a delay in release at acidic pH; however, at alkaline pH, it showed a significant improvement in API solubility, which was confirmed in the tests performed [54]. On the other hand, Soluplus shows the lowest solubility in acidic pH and the highest in alkaline pH; in the study, it was shown that the systems containing the polymer showed better solubility at higher pH, which confirms the assumption that the solubility of the entire system will depend on the solubility of the polymer used to compose the physical mixture [55,56]. The obtained results indicate the potential development of formulations containing carvedilol as an active substance based on selected polymers, allowing API release in a selected pH-dependent environment.…”
Section: Resultssupporting
confidence: 64%
“… 1 3 The solubility of a drug substance is one of the significant parameters impacting absorption 4 as well as bioavailability, defined as the fraction of the administered dose of a drug that enters the systemic circulation, thereby accessing the site of action. 5 It is reported that EFV has a low aqueous solubility (9.2 μg mL –1 ) (pH 8.7) at 25 °C, 6 8 higher as the pH increases above 9, for the proton loss on the carbamate group’s amine. 6 Unfortunately, EFV tends to be eliminated in the human systemic circulation before the dissolution and absorption into the systemic circulation processes are completed, therefore requiring an increased dosage to achieve therapeutic levels in the body, often implying adverse effects for the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophilic polymers, such as Soluplus ® , hydroxypropyl methylcellulose phthalate (HPMCP), and polyvinyl alcohol (PVA) enhance supersaturation and inhibit precipitation by employing hydrophobic interactions with drugs or intermolecular interactions, such as hydrogen bonds, ionic bonds, and van der Waals interactions [7][8][9][10]. Solvent evaporation and melting are mainly used to prepare amorphous SDs.…”
Section: Introductionmentioning
confidence: 99%